RESPONSE OF DIFFERENT VARIETIES OF FABA BEAN TO PLANT SOURCE ORGANIC FERTILIZERS - & Al-Baldawi, Dhary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A  Field experiment was conducted during winter season at 2015 – 2016 at the experimental farm, department of Field Crop, College of Agriculture, University of Baghdad / Jadriyah to investigate effect of Organic Fertilizers preparation from weed plants on various broad bean varieties behavior and relationships with seed yield and its components. A randomized complete block design (RCBD) arranged according to split-plots used with three replicates including four organic fertilizers prepared from weeds Licorice (Glycyrrhiza glabra), Mallow (Malva rotundifolia), Purslane (Portulaca oleracea), European Heliotropic (Heliotropium europaeum), chemical fertilizer and control (without fertilizer) treatments, main plots included three varieties of Bean (Netherlands, Spanish and Locality ). The results showed that application of fertilizers significantly effect on studied characters, the treatment of Glycyrrhiza glabra gave higher rate of yield 3417 Kg ha-1, and There were no significant differences between Glycyrrhiza glabra and chemical fertilizer (NPK) at seed yield. Application of NPK showed highest No. of branches per plant, leaf area, thus reduction the flower portion percentage (4.02%) and increase pod numbers per plant and seed number per pod compared to control treatment. The results showed significant differences between varieties. The Spanish variety gave highest means of No. of branches per plant and leaf area per plant, thus reducing the flower portion and increase the number of pods per plant, number of seeds per pod and seed yield 3231 Kg ha-1. The Netherland variety gave higher weight of 100 seeds 47.94 g than the other varieties. Also, the most of characters were significantly influenced by interaction between varieties and fertilizers.